Strategi Komunikasi Dakwah Badan Penyelenggara Jaminan Produk Halal Dalam Edukasi Sertifikasi Halal Pada UMKM Kuliner Kota Medan - Agam Arsyad; Elfi Yanti Ritonga (STAI Bumi Silampari, 2025)
This study aims to analyze the communication strategy of da'wah carried out by the Halal Product Guarantee Agency (BPJPH) in educating culinary Micro, Small, and Medium Enterprises (MSMEs) in Medan City regarding the importance of halal certification. The research method used is a qualitative approach with in-depth interview techniques and document analysis. The results of the study show that BPJPH implements a communication strategy through various media, including direct socialization, use of social media, and collaboration with various institutions such as local governments, banks, and religious organizations. Social media, especially Instagram and WhatsApp, are used to expand the reach of halal certification education. In addition, training and mentoring programs by the Halal Product Process Assistant (P3H) are key factors in helping MSMEs understand and meet halal certification requirements. The main obstacles in implementing this strategy are the lack of understanding of business actors about the benefits of halal certification and limited resources in meeting administrative requirements. Therefore, efforts are needed to improve education and digitize services so that the halal certification process is more accessible to MSMEs.